Whiteness, Class and the Legacies of Empire - Tyler, K. author. aut Link
X, 241 p.
Keywords: This book explores why it is white ethnicity has been rendered invisible, arguing that contemporary people's conceptions of themselves are conditioned by, and derive from, the unknown and forgotten legacy of a colonial past that cannot be confined to the past.